International Handbook of Engineering Education Research - Aditya Johri (Routledge, 2023)
Winner of the 2024 American Educational Research Association (AERA) Division I Outstanding Research Publication AwardThis comprehensive handbook offers a broad overview of contemporary research on engineering education and its practical application. Over the past two decades, the field of engineering education research (EER) has become a vibrant and impactful community with new journals, conferences, and doctoral and research programs established across the globe. The increased interest in this area has helped improve the education and training of the next generation of engineers, as well as supporting growth in the use of technology for teaching and learning, increased attention to broadening participation, diversity and inclusion in the field, and a wide international expansion of the field.Drawing on the work of 100 expert contributors from over 20 countries, this volume covers both emergent and established areas of research within engineering education, giving voice to newcomers to the field as well as perspectives from established experts. Contents include: Sociocognitive and affective perspectives on engineering education. Technology and online learning in engineering education. Cultural and ethical issues including diversity, equity, and inclusion in engineering education. Curriculum design, teaching practices, and teacher education at all levels. Research methods and assessment in engineering education. This book offers an innovative and in-depth overview of engineering education scholarship and practice, which will be of use to researchers in engineering education, engineering educators and faculty, teacher educators in engineering education or STEM education, and other engineering and STEM-related professional organizations.The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license.